The fundamentals of health economics and its application in the provision of vascular surgery in the UK. (September 2021) - Osman, Fatima; Ravendren, Andrew; Mohammed, Idhrees; Bashir, Mohamad
Health economics offers a lifeline to policymakers as a way of improving health outcomes in the face of increased monetary constraints. Doctors are uniquely placed in healthcare delivery where they have a pertinent influence on both supply and demand for healthcare provisions. Every clinical decision made by doctors is also an economic decision, and the true cost of offering a scarce healthcare resource includes not being able to fund alternative therapies and hence, foregoing its benefit. Technology and innovation in medicine is seeing an increase in potential therapies; however, how well do they perform against the current gold standard and are they worth the additional cost? A personalized and patient-centered approach to medicine has paved the way for a holistic health outcome measure, quality-adjusted life years, which is predominately used by United Kingdom resource allocators. Aortic surgical interventions are resource-intensive, and recent trends have shown the growing economic burden as yearly costs continue to climb. Health economic models are not without their weaknesses and it is important that future analyses assess the impact on society, distributional consequences, and the value of collecting more information to reduce the uncertainty of the economic result.